The Characteristics of Children with UTI Due to ESBL-producing Bacteria at Dr. Soetomo General Hospital, Surabaya - Ida Fitriawati; Manik Retno Wahyunitisari; Risky Vitria Prasetyo; Dwiyanti Puspitasari; Tuksin Jearanaiwitayakul (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Urinary tract infection (UTI) by extended-spectrum beta-lactamase-producing bacteria often results in a delay in obtaining appropriate antibiotics. The information on patients’ clinical characteristics is necessary for early recognition and the selection of empiric antibiotic therapy. This study aims to investigate the clinical characteristics and the length of therapy of patients with urinary tract infections by those resistant bacteria.Method: This study utilizes a cross-sectional design. Medical records of hospitalized children aged 1-18 months with UTI due to ESBL-producing bacteria at Dr. Soetomo general hospital between January 1, 2017 - July 20, 2020, were reviewed retrospectively. Variables of interest were the demographic data, underlying diseases, causative organism, clinical presentation, maximal body temperature, and length of antibiotic therapy.Results: Among 37 patients enrolled, 25 patients were female. The incidence of urinary tract infection in children was dominated by age 1-12 months old (37.8%). Urological abnormalities were presented in 62.2% of patients. ESBL-producing Escherichia coli was the most common isolated uropathogen (62.2%). High fever was found in 10/28 patients (35.7%). In 17 patients (45.9%), the total duration of antibiotic therapy was 8-14 days.Conclusion: In children with UTI, especially in the infant group, who had urological abnormality or present with a high fever, and who do not respond to empiric therapy should be suspected of developing UTI due to ESBL-producing bacteria.